The Effect of Work Motivation and Organizational Culture on Employee Performance at PT. Telkom Padang Branch - Benny Ahmad Yusuf; Rini Sarianti; Chichi Andriani (Greenation International Journal of Tourism and Management, 2023)
This study aims to analyze the influence of Work Motivation and Organizational Culture on Employee Performance of PT. Telkom Padang branch . This research was conducted at PT. Telkom Padang branch . The population in this study were all employees of PT. Telkom Padang branch totaling 142 people . The sampling technique used was a proportional cluster sampling technique so that a sample of 79 people was obtained. The data analysis technique used is regression analysis . Hypothesis testing in this study was carried out with the f test and t test. The results of the study show that : (1) Work motivation has a significant positive effect on Employee Performance at PT Telkom Padang branch , (2) Organizational Culture has a significant positive effect on Employee Performance at PT Telkom Padang branch .